2003
DOI: 10.1074/jbc.m302109200
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking in the Living Cell Locates the Site of Action of Oxazolidinone Antibiotics

Abstract: Oxazolidinone antibiotics, an important new class of synthetic antibacterials, inhibit protein synthesis by interfering with ribosomal function. The exact site and mechanism of oxazolidinone action has not been elucidated. Although genetic data pointed to the ribosomal peptidyltransferase as the primary site of drug action, some biochemical studies conducted in vitro suggested interaction with different regions of the ribosome. These inconsistent observations obtained in vivo and in vitro have complicated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
93
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 58 publications
4
93
1
1
Order By: Relevance
“…In contrast, recent studies using an elegant in vivo cross-linking approach revealed the PTC as the bone fide drug target (12,13). These latter studies are consistent with the observation that drug resistance in both archaea and bacteria arises through mutation of nucleotides located within the PTC [ Fig.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, recent studies using an elegant in vivo cross-linking approach revealed the PTC as the bone fide drug target (12,13). These latter studies are consistent with the observation that drug resistance in both archaea and bacteria arises through mutation of nucleotides located within the PTC [ Fig.…”
supporting
confidence: 75%
“…S5b) (37). In this regard, we note however that a ⌬lepA strain has an identical IC 50 for oxazolidinones as the wild-type strain (12), suggesting that the binding of LepA is a consequence, rather than a cause, of the functional state induced by the oxazolidinones.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Binding of linezolid to this area was subsequently supported by other mutagenesis studies but could not be verified by antibiotic footprinting, a technique that has been used successfully to localize ribosomal binding sites for other antibiotics. Cross-linking studies with linezolid derivatives also pointed to a location at the PTC (12,46). In 2008, this site was confirmed by crystal structures of linezolid bound to the 50S ribosomal subunit from the archaeon Haloarcula marismortui (36) and from the bacterium Deinococcus radiodurans (95).…”
Section: The Linezolid Binding Site On the Ribosomementioning
confidence: 83%
“…[2][3][4][5][6] With the increase in resistance of bacteria to antibiotic treatment, attention was given on developing novel approaches to antimicrobial therapy. [7][8][9][10][11][12][13] We have previously reported the significant antifungal activity of a series of sulfonamide-1,2,4-triazole derivatives against a series of micromycetes, compared to the commercial fungicide bifonazole. These compounds have also shown a comparable bactericidal effect to that of streptomycin but better activity than chlorampenicol respectively against various bacteria.…”
mentioning
confidence: 99%